Analisis Istihsan Atas Pertimbangan Hakim Terhadap Saksi Non Muslim Pada Perkara Perceraian - Zaman, Misbahul (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2018)
Verification in the Religion Court is important because the court upholds law and justice based on no other evidence, including in civil cases, such as divorce. One of the proofs is a witness testimony. The majority of Islamic law experts like Imam Malik, Imam al-Shafi'i or Imam Ahmad ibn Hanbal agreed that a witness must be a Muslim, so that in a case witnessed by someone who is not Muslim, his testimony is deemed invalid. This article wants to see a case of establishing non-Muslim witnesses in a divorce case in the Sidoarjo Religious Court by using descriptive analysis, which is systematically describing the facts and characteristics of the object studied by the later analysis and using the istihsan theory. Based on the analysis, the Sidoarjo Religious Court in Case No. 1889/Pdt.G/2017/PA.Sda. has received the status of a non-Muslim witness because it has fulfilled formal requirements in a civil procedure law. In line with istihsan theory, non-Muslim testimony is permissible because of the development of the present era and its greater difficulties so that it can be accepted in religious courts. If it is forced that witnesses to be Muslim, then justice seekers will be harmed and have difficulties. [Pembuktian di muka peradilan Agama merupakan hal yang penting sebab pengadilan menegakkan hukum dan keadilan tidak lain berdasarkan pembuktian, termasuk dalam perkara perdata, seperti perceraian. Salah satu alat bukti keterangan saksi. Mayoritas para pakar hukum Islambaik Imam Malik, Imam al-Shafi’i ataupun Imam Ahmad ibn Hanbal menyepakati bahwasannya seorang saksi harus beragama Islam, sehingga apabila dalam suatu perkara yang disaksikan oleh orang yang bukan beragama Islam, maka kesaksiannya dipandang tidak sah. Tulisan ingin melihat satu kasus penetapan saksi non-muslim dalam perkara perceraian di Pengadilan Agama Sidoarjo dengan menggunakan analsisi deskriptif, yaitu menggambarkan secara sistematis fakta dan karakteristik objek yang diteliti suntuk kemudian dianalisis mengguanakan teori istihsan. Berdasarkan analisis, Pengadilan Agama Sidoarjo dalam perkara Nomor. 1889/Pdt.G/2017/PA.Sda menerima status saksi non muslim karena sudah memenuhi syarat-syarat formil dalam hukum acara perdata. Sejalan dengan teori istihsan, kesaksian non-muslim diperbolehkan karena melihat perkembangan zaman yang sekarang ini dan lebih besar maslahatnya sehingga bisa diterima di pengadilan agama. Jika memaksakan saksi harus yang beragama Islam, maka para pencari keadilan akan dirugikan dan mengalami kesulitan.]